Peran Faktor-faktor Psikologis terhadap Depresi pada Pasien Diabetes Mellitus Tipe 2 - Donsu, Jenita DT; Hadjam, M Noor Rochman; Asdie, Ahmad Husain; Hidayat, Rahmat (Faculty of Psychology, Universitas Gadjah Mada, 2014)
Depression has strong relationship with diabetes mellitus and the aspect of psychology has influence toward the diabetes patient as control. This research aimed to find out the role of psychological factors in dealing with depression suffered by patient of DM-2 and to see the dynamics of both direct and indirect relationship of psychological factors toward the depression of DM-2 patient. The main model is a model that can bring effect of mediation between social support and depression caused by DM-2. Optimism can provide mediating effect of the relationship between social support and self-esteem. Resilience can provide mediating effect of the relationship between social support and self-esteem. Similarly, self-esteem acts as the mediator of the relationship between optimism and resilience toward the depression of DM-2 patient. The result of estimation parameter test showed the direct relationship between social support toward optimism (0.717), resilience (0.811), self-esteem (0.269) and depression (-0.210) and the direct role to depression (-0.397). The higher social support and self-esteem will cause the higher optimism and resilience. On the other hand, the role of self-esteem showed negative coefficient. On the other hand, the role of self-esteem to depression showed a negative coefficient is, the higher self-esteem will be followed by the decrease of depression in patient with DM-2. Keywords: depression, optimism, resilience, self-esteem, social support, DM-2